Molecular Epidemiology of Mycobacterium tuberculosis To Describe the Transmission Dynamics Among Inuit Residing in Iqaluit Nunavut Using Whole-Genome Sequencing. (13th April 2020) - Alvarez, Gonzalo G; Zwerling, Alice A; Duncan, Carla; Pease, Christopher; Van Dyk, Deborah; Behr, Marcel A; Lee, Robyn S; Mulpuru, Sunita; Pakhale, Smita; Cameron, D William; Aaron, Shawn D; Patterson, Michael; et al.
Abstract: Background: In the last decade, tuberculosis (TB) incidence among Inuit in the Canadian Arctic has been rising. Our aim was to better understand the transmission dynamics of TB in this remote region of Canada using whole-genome sequencing. Methods: Isolates from patients who had culture-positive pulmonary TB in Iqaluit, Nunavut, between 2009 and 2015 underwent whole-genome sequencing (WGS). The number of transmission events between cases within clusters was calculated using a threshold of a ≤3 single nucleotide polymorphism (SNP) difference between isolates and then combined with detailed epidemiological data using a reproducible novel algorithm. Social network analysis of epidemiological data was used to support the WGS data analysis. Results: During the study period, 140 Mycobacterium tuberculosis isolates from 135 cases were sequenced. Four clusters were identified, all from Euro-American lineage. One cluster represented 62% of all cases that were sequenced over the entire study period. In this cluster, 2 large chains of transmission were associated with 3 superspreading events in a homeless shelter. One of the superspreading events was linked to a nonsanctioned gambling house that resulted in further transmission. Shelter to nonshelter transmission was also confirmed. An algorithm developed for the determination of transmission events demonstrated very good reproducibility (κ score .98, 95% confidence interval, .97–1.0). Conclusions: Our study suggests that socioeconomic factors, namely residing in a homeless shelter and spending time in a gambling house, combined with the superspreading event effect may have been significant factors explaining the rise in cases in this predominantly Inuit Arctic community. Abstract : A homeless shelter was the epicenter of an outbreak in 2010 in Iqaluit, which led to the peak of active TB disease observed in the Territory the following year. The extensive spread of TB transmission after the initial peak was an unexpected finding and greater than anticipated.